Contrastive Analysis of Interjections in Indonesian and Mandailing Batak Language - Rina Devianty; Nila Riana Harahap (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
This study provides a contrastive analysis of interjections in the Indonesian and Mandailing Batak languages, focusing on their morphological characteristics. By comparing these two languages, we aim to highlight their similarities and differences in the use and formation of interjections. This analysis is limited to a morphological review to prevent overlap with topics related to verb types and verb formation processes. Utilizing both descriptive qualitative research methodology and comparative-contrast descriptive methodology, we systematically compare the interjection morphology in both languages. The methodologies differ in their application: the descriptive qualitative approach involves detailed observations and descriptions of interjection usage, while the comparative-contrast approach focuses on identifying and analyzing the distinctions and similarities between the languages. The primary data source comprises example sentences created by the researcher, ensuring linguistic acceptability. The researcher's specific tasks include selecting relevant sentences, analyzing their morphological structures, and categorizing the interjections. Data collection encompasses the specific interjection systems of each language, and each grammatical category's realization is examined. Contrasts are drawn based on the analysis outcomes after thorough data collection.